An isochronic substitution benefit study of the effects of screen time on the cognitive abilities of 3–6 children - Zhenya, Chang; Aifeng, Zhu; Ling, Wang (Frontiers in Psychology, 2024)
Purpose To investigate the impact of substituting screen time with other activities on children's cognitive ability. Method A total of 583 children (299 males and 284 females), aged 3–6 years, were selected as participants. Correlation, regression, and isochronic substitution analyses were used. Results Screen entertainment time on TV (SET_TV) was negatively associated with children's math ability. However, screen learning time on other electronic devices besides TV (SLT_OED) and non-screen learning time by learning alone (NSLT_LA) were positively associated with math ability and language ability. After controlling for gender, age, and family socio-economic status, SET_TV remained negatively associated with math ability, while NSLT_LA remained positively correlated. Furthermore, substituting 10 min of SET_TV with NSLT_LA resulted in an increase of 0.55 in language ability and 0.87 in math ability. Similarly, substituting SLT_OED, sleeping at home, and exercising outside of kindergarten for 10 min of SET_TV resulted in an increase of 0.90, 0.43, and 0.61 in math ability, respectively. Conclusions There are cognitive benefits when screen recreation time is replaced with screen learning time, non-screen learning time, sleep time, and exercise time, with the highest benefits observed when screen recreation time is substituted with NSLT_LA.